2019
DOI: 10.1016/j.apenergy.2019.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the cost of leaving the Paris Agreement via the integration of life cycle assessment, energy systems modeling and monetization

Abstract: Current energy systems models focus on cost minimization with a bound on some greenhouse gas emissions. This limited environmental scope can lead to mixes that are not consistent with our sustainable development. To circumvent this limitation, we here make use of the concept of monetization and life cycle assessment to quantify the indirect costs of electricity generation in the design of energy systems. Applying our approach to the United States, we found that the indirect costs of electricity generation coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…One of the most critical factors is the energetic footprint of materials and chemicals, even though materials enter into the system as matter, its production and/or assembly has an energetic cost considered in the ESA as energy fund-resource, in many cases at different geographical locations. For example, an installed Photovoltaic System in Europe but produced abroad has an energetic burden to society in energy terms, however, the economic analysis includes the disparity in salaries and services costs between countries, which can mislead sustainability studies [57].…”
Section: Analogical Model (Am)mentioning
confidence: 99%
“…One of the most critical factors is the energetic footprint of materials and chemicals, even though materials enter into the system as matter, its production and/or assembly has an energetic cost considered in the ESA as energy fund-resource, in many cases at different geographical locations. For example, an installed Photovoltaic System in Europe but produced abroad has an energetic burden to society in energy terms, however, the economic analysis includes the disparity in salaries and services costs between countries, which can mislead sustainability studies [57].…”
Section: Analogical Model (Am)mentioning
confidence: 99%
“…Several authors clarified that the PEM and LCA coupling is suitable to study one or two closely related sectors with 5 to 20 products [43,44]. This is true for all reviewed case studies which applied PEM and LCA, with focus on one sector of energy production [22,[29][30][31][44][45][46][47][48][49][50][51], or two sectors of energy production and waste management [52,53] or energy production and agriculture/forest/crop growing [39,41,[54][55][56][57][58][59][60][61][62].…”
Section: Operational Modelmentioning
confidence: 99%
“…All of the reviewed case studies expanded the product system boundary by either increasing unit processes or including relevant products and co-products. Some studies made it very clear on the inclusion of extended unit processes [22][23][24][25][26], while others did not clearly identify the unit processes of a product system's life cycle [27][28][29][30][31][32][33][34]. In terms of products and co-products, the system boundary was extended to at least two products in all reviewed studies.…”
Section: System Boundarymentioning
confidence: 99%
“…Examples of the mutatis mutandis assumption can be found in several studies [23][24][25][26][27][28][29][30][31][32][33][34][40][41][42][43][44][45] (Refer to Table 2). In these studies, the marginal products or technologies were identified, with determined affected scales.…”
Section: System Boundarymentioning
confidence: 99%